The impact of the COVID-19 pandemic on illicit drug supply, drug-related behaviour of people who use drugs and provision of drug related services in Georgia: results of a mixed methods prospective cohort study - David Otiashvili; Tamar Mgebrishvili; Ada Beselia; Irina Vardanashvili; Kostyantyn Dumchev; Tetiana Kiriazova; Irma Kirtadze (BMC, 2022)
Abstract Background This study examines the effects of COVID-19 related restrictions on the supply of illicit drugs, drug-use behaviour among people who use drugs (PWUD) regularly (at least weekly), and drug-related service provision in Tbilisi, Georgia. Methodology In this mixed methods study, a cohort of 50 Georgian PWUD recruited through a snow-ball sampling participated in a bi-weekly online survey in April-September, 2020. They also took part in the qualitative telephone interviews at 12- and 24-week follow-up time points. In addition, four key informants (field experts) were interviewed monthly to assess their perceptions of changes in the illicit drug market and drug service delivery. Results Mean age in the sample was 36 (range 18-60); 39 (78%) were males. Perceived availability of drugs was reduced during the lockdown, and many PWUD switched to alternative substances when preferred drugs were not available. On average, participants used significantly fewer substances over the course of the study, from 3.5 substances in the preceding 14 days to 2.1 (aOR 0.92; 95% CI 0.90-0.94). Consumption of cannabis products declined significantly (aOR 0.89; 95% CI 0.84-0.95), likewise alcohol (aOR 0.94; 95% CI 0.88-1.0), diverted medicinal methadone (aOR 0.85; 95% CI 0.8-0.9) and diverted medicinal buprenorphine (aOR 0.91; 95% CI 0.84-0.99). PWUD cited fewer contacts with drug dealers, the lack of transportation, and the lack of conventional recreational environment as the main reasons for these changes. When access to sterile injection equipment was limited, PWUD exercised risk-containing injection behaviours, such as buying drugs in pre-filled syringes (aOR 0.88; 95% CI 0.80-0.96). Harm reduction and treatment programs managed to adopt flexible strategies to recover services that were affected during the initial stage of the pandemic. Conclusions COVID-19-related restrictive measures mediated specific changes in supply models and drug-use behaviours. While adjusting to the new environment, many PWUD would engage in activities that put them under increased risk of overdose and blood-borne infections. Harm reduction and treatment services need to develop and implement protocols for ensuring uninterrupted service delivery during lockdowns, in anticipation of the similar epidemics or other emergency situations.